Fluorogenic properties of 4-dimethylaminocinnamaldehyde (DMACA) enable high resolution imaging of cell-wall-bound proanthocyanidins in plant root tissues - Chowdhury, Jamil; Ferdous, Jannatul; Lihavainen, Jenna; Albrectsen, Benedicte Riber; Lundberg-Felten, Judith (Frontiers in Plant Science, 2023)
Proanthocyanidins (PAs) are polymeric phenolic compounds found in plants and used in many industrial applications. Despite strong evidence of herbivore and pathogen resistance-related properties of PAs, their in planta function is not fully understood. Determining the location and dynamics of PAs in plant tissues and cellular compartments is crucial to understand their mode of action. Such an approach requires microscopic localization with fluorescent dyes that specifically bind to PAs. Such dyes have hitherto been lacking. Here, we show that 4-dimethylaminocinnamaldehyde (DMACA) can be used as a PA-specific fluorescent dye that allows localization of PAs at high resolution in cell walls and inside cells using confocal microscopy, revealing features of previously unreported wall-bound PAs. We demonstrate several novel usages of DMACA as a fluorophore by taking advantage of its double staining compatibility with other fluorescent dyes. We illustrate the use of the dye alone and its co-localization with cell wall polymers in different Populus root tissues. The easy-to-use fluorescent staining method, together with its high photostability and compatibility with other fluorogenic dyes, makes DMACA a valuable tool for uncovering the biological function of PAs at a cellular level in plant tissues. DMACA can also be used in other plant tissues than roots, however care needs to be taken when tissues contain compounds that autofluoresce in the red spectral region which can be confounded with the PA-specific DMACA signal.